Babies born with ambiguous genitalia: Developing an educational resource for Australian midwives. Issue 1 (February 2023) - Hanna, Chloe A.; Cummins, Allison; Fox, Deborah
Abstract: Problem and background: The birth of a baby with ambiguous genitalia is rare and usually unexpected. Parents often receive inconsistent language from health-professionals after the birth. Initial interaction with the birth team has long-term consequences for families with babies born with ambiguous genitalia. Aim: Understand the current practices on the day of birth and explore knowledge gaps for midwives regarding babies born with ambiguous genitalia. Develop educational content that can enable midwives to respond appropriately when the sex of a baby is unclear. Methods: This study included two phases, utilising qualitative descriptive research design with semi-structured interviews to understand the experiences of midwives caring for babies with ambiguous genitalia and their families. The findings informed the development a midwifery educational resource using these qualitative findings. Findings: Our analysis of 14 interviews with Australian midwives identified that they had no formal education to support families with a baby with ambiguous genitalia. Emotional support, advocacy and medical information translation were areas midwives perceived as essential skills to support these families. Discussion: Midwives provide a unique role in parental birth experiences. Themes that arose emphasised their psychosocial support role but lacked formal education and guidance on this topic. Midwives had learnt from the media about babies born with ambiguous genitalia and wanted evidence-based education to support parents. Midwife education focusing on both psychosocial and clinical care for parents and their baby with ambiguous genitalia is crucial. Conclusion: Midwives can play a pivotal role in supporting parents with a baby with ambiguous genitalia. Themes from this qualitative study informed the development of a midwifery education digital resource.